Identification of Sand flies of the Subgenus Larroussius based on Molecular and Morphological Characters in North Western Iran - A Absavaran; Y Rassi; P Parvizi; MA Oshaghi; MR Abaie; S Rafizadeh; M Mohebali; Z Zarea; E Javadian (Tehran University of Medical Sciences, 2009)
Background: The adult female sand flies (Diptera: Psychodidae) of the subgenus Larroussius are important vectors of Leishmania infantum (Kinetoplastida: Tripanosomatidae) in Meshkinshahr district, Northwest of Iran. Four Phlebotomus (Larroussius) species are present in this area, i.e. Phlebotomus (Larroussius) kandelakii, P. (La.) major, P. (La.) perfiliewi and P. (La.) tobbi. The objective of the present study was to identify and distinguish the females of P. perfiliewi, P. major and P. tobbi, in this district. Methods: Adult sand flies were collected with sticky papers, CDC light traps, and aspirator in 2006. Individual sand flies of this four species from thirty different locations were characterized morphologically and by comparative DNA sequences analyses of a fragment of mitochondrial gene Cytochrome b (Cyt b) and nuclear gene Elongation Factor 1- alpha (EF-1α). PCR amplification was carried out for all three species P. major, P. perfiliewi and P. tobbi in the subgenus Larroussius. Results: Phylogenetic analyses of P. major populations in this study displayed two different populations and genetic diversity. Spermathecal segment number, pharyngeal armature and other morphological characters of these three species were examined and found to present consistent interspecific differences. Conclusion: According to our findings, the phylogeny of Cyt b and EF-1α haplotypes confirms the relationships between P. major, P. tobbi and P. perfiliewi as already defined by their morphological similarities.